Canoeist training in Germany: From the base to the high level elite - Caballero, J. D. (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
In order to talk about training in canoeing in calm waters in Germany we should go back to the division that this country suffered after World War II. On one hand, there was a federal and democratic Germany, and on the other hand, a communist and a dictatorial Germany. If we go back to the history of these two countries, we can see that the two nations have a great track record. This is largely due to the influence that the former GDR or East Germany had in canoeing from the 60s to the early 90s. Leaving aside the surplus of doping that shook the country, the truth is that all the innovations introduced by the GDR in the sporting world made a breakthrough and created the base of what canoeing in calm waters is today in Germany. The communist system had a large and well organised structure of "talent identification". It also had very specific and detailed guidelines for clubs and training centres so that the athletes would reach their maximum performance in the senior category. Nowadays, after the union of the two Germanys, the old training model of the former Democratic Republic lives on the foundations of the current German federation of canoeing (Deutsche Kanu Verband or DKV) The basic principles are based on a long term planning model of the athletes, seeking a joint effort between the regional federations (Bundesland) and the clubs. Their aim is to train athletes in the lower categories through indicative workloads, which facilitate the work of the clubs when organizing and structuring the training. The model is simple, ranging from the general to the specific. In this chapter we will see, in a general way, the German model of training, from the lower categories to the senior category. We will define training paces and we will take into account the physical needs of each athlete. For this reason, we will briefly see the sensitive stages and the way of preparation. Note that in this chapter we will see the different training methods provided by the Federation to the different clubs for the development of their paddlers. In the following pages our main focus will be on the preparation for the average distance since, because of the absence of a clear official model provided by the German federation for the preparation of the 200 meters, the information here disclosed would be the opinion of an author and may not match the "German model of training". This means that, although references will be made, the rhythms and volumes of training will be more related to the average distance than to the short one. The information given here appears partly in the training manuals created by the German federation. Data and Nomenclature are specific and focused on canoeing in calm waters, but they cannot be absolute from a physiological, scientific, and/or literary point of view.